Solvent Effects On Alkaline Hydrolysis Of N-Benzylphthalimide In Mixed Water-Acetonitrile And Mixed Water-N,N-Dimethylformamide - Ariffin, Azhar; Khan, M.N.; Ye, C.M. (2005)
The nucleophilic second-order rate constant (kappa(OH)) for the reaction of OH- with N-benzylphthalimide appears to follow a reaction mechanism similar to that for reactions of OH with phthalimide and its N-alkylphthalimides. The rate of hydrolysis reveals an insignificant contribution of water-catalysed cleavage of NBPT compared with its hydroxide ion catalysed reaction. The observed pseudo first-order rate constant, kappa(obs), for alkaline hydrolysis of NBPT decreases with increase in the content of organic cosolvents (up to 70%, nu/nu) in mixed water-CH3CN and water-DMF solvents.